2012
DOI: 10.1109/tse.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Measurement of Software Process Improvement—A Systematic Literature Review

Abstract: BACKGROUND-Software Process Improvement (SPI) is a systematic approach to increase the efficiency and effectiveness of a software development organization and to enhance software products. OBJECTIVE-This paper aims to identify and characterize evaluation strategies and measurements used to assess the impact of different SPI initiatives. METHOD-The systematic literature review includes 148 papers published between 1991 and 2008. The selected papers were classified according to SPI initiative, applied evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
153
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(170 citation statements)
references
References 251 publications
(1,274 reference statements)
0
153
0
17
Order By: Relevance
“…Indeed, a systematic literature review of 148 papers published between 1991 and 2008 [27] revealed that Effort and Productivity were defined as success indicators in 63% of studies of process improvement initiatives. In the simplest terms, effort is the time spent by the team during the development process and productivity is its output size in terms of KLOC (kilo lines of code) [28].…”
Section: Project Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a systematic literature review of 148 papers published between 1991 and 2008 [27] revealed that Effort and Productivity were defined as success indicators in 63% of studies of process improvement initiatives. In the simplest terms, effort is the time spent by the team during the development process and productivity is its output size in terms of KLOC (kilo lines of code) [28].…”
Section: Project Efficiencymentioning
confidence: 99%
“…While much research has addressed the definition and measurement of success in industrial software engineering undertakings [3], [4], [5], so far little attention has been paid to the same problem in academic context. This article explores how assessment criteria used for IT deliverables can be translated into an academic grading context and aims to introduce a set of metrics, and measures for evaluation of projects developed by students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such SPMS are core initiatives (i.e. process frameworks besides best practices and tools [7]) into the Software Process Improvement (SPI) approach. According to [7] SPI refers to "a systematic approach to increase the efficiency and effectiveness of a software development organization and to enhance software products".…”
Section: Introductionmentioning
confidence: 99%
“…process frameworks besides best practices and tools [7]) into the Software Process Improvement (SPI) approach. According to [7] SPI refers to "a systematic approach to increase the efficiency and effectiveness of a software development organization and to enhance software products". However, according to [4] these SPI initiatives "were not written for small projects, small development organizations, or companies with between 1 and 25 employees, and are consequently difficult to apply in such settings".…”
Section: Introductionmentioning
confidence: 99%